Fuzzy Logic Controller Effectiveness Evaluation through Comparative Memberships for Photovoltaic Maximum Power Point Tracking Function - Hussain Attia (Institute of Advanced Engineering and Science, 2018)
Maximum Power Point Tracking (MPPT) is an important objective needed to gain maximum power from solar photovoltaic panel during the weather condition variation. Many studies and solutions are proposed in literature, most of them focus on the type of algorithm which adopted for MPP tracking through using same driver i.e. DC-DC Boost converter. Among these algorithms, Fuzzy Logic Controller (FLC) demonstrates high quality performance by fast tracking response and robust effectiveness. This paper proposes a FLC by a new harmony of the input and the output variables through comparative study to the controller tracking behavior. To track the MPP, the proposed solution controls the change of duty cycle for PWM gate drive pulses width variation to drive the designed Buck-Boost DC-DC converter. MATLAB/Simulink software is selected to simulate the introduced controller. The simulation results are reflecting the promising indications to adopt the presented proposal as an effective MPPT system for practical applications.